Research on the Orderliness Synergy Between Conventional and Nonconventional for Energy Transition in China - Liu, Pingkuo; Lu, Cunyu; Zhao, Ruiqi (Frontiers in Energy Research, 2022)
Many industrialized countries are pursuing energy transition, but their focuses are different. The orderliness synergy as a unique aspiration of the current energy transition is emphasized in this article by constructing an orderliness-synergy evaluation model and selecting a dataset covering the period of 2011–2018 from Industrial Scale, Economic Benefit, Social Contribution, and Growth Potential of China to calculate the comprehensive development level and the orderliness-synergy degree of both the conventional energy industry and the nonconventional one. A novel evaluation model with stock-increment attributes is built to measure the resource storage and the growth rate systematically and to further analyze their driving forces. The results reveal that 1) the overall orderliness-synergy degree of these two sub-industries shows an upward trend year by year; however, there are some significant differences among them. 2) China’s energy transition has shown a dramatic promotion in the structural upgrading, while the momentums of these two sub-industries show a shift from the stock–resource–contribution advantage to the increment–resource–contribution advantage. 3) The actual stock-increment contribution coefficient values of these two sub-industries have not reached the development expectations of industrial performances, and there is still reasonable space for the structural optimization. Finally, policy implications are discussed.